Disability, Intersectionality, Child Welfare and Child Protection: Research Representations - Thomas, Cate; Flynn, Susan; Slayter, Elspeth; Johnson, Lisa (Scandinavian journal of disability research : SJDR, 2023)
Considerations of the disability community within child welfare generally and the child protection sector specifically are well-served using an intersectional analytical lens. We aimed to determine how intersectionality is listed in the child welfare literature in the context of disability and to describe how and to what extent researchers integrate, embed, and engage intersectionality in the conduct of their research. This critical literature review was informed by scoping review strategies, with qualitative thematic analysis to help us to produce descriptive patterns. It was unexpected that less than half of the articles engaged in the intersectionality of child welfare or child protection and disability, and in only 23.8 percent of the sample articles was this explicitly engaged. Our primary finding is that researchers use the term intersectionality but are not always rigorously engaging with the concept methodologically. We recommend the use of 'strong intersectionality' methodological techniques and deeper consideration of disability as a social identity in this research arena. Keywords: intersectionality, disability, child protection, child welfare, scoping review, application of intersectionality